THE PRESENT CONDITION AND PROSPECTS OF MILLET SEED-GROWING IN THE ORENBURG REGION - L. A. Mukhitov; A. A. Zorov (Зерновое хозяйство России, 2018)
The article has presented the analysis of varietal sowings in the Orenburg region during 2009-2013. It has estimated the change of a share of varietal and row sowings of millet. The analysis of the areas of various categories of millet sowings has determined a range of the share of varietal and row sowing on the general area, which was connected with availability of basic varietal seed material. During the 5-year period the share of varietal sowings ranged between 64.1-72.9 %. The article has given a volume of original and basic sowing material production in FSBSI “Orenburg RIA” and FSTI “Sovetskaya Rossiya”. Each year from 2400 to 3500 species of millet are subject to selection and culling. This amount of selected varieties provides the production of basic seed of Orenburg breeding with sufficient amounts. The assessment of categories of used seed material on the parts of the Orenburg region has been given. In the Orenburg region the sowing material of millet is presented with 0.4 th. htw of original seeds (3.5% of the whole amount of sown seeds), 0.3 th. htw of basic seeds (2.7%), 0,2 th. htw of seeds of the 1-st reproduction (1.8%), 0,1 th. htw of seeds of the 2-nd reproduction (0.9%), 1.3 th. htw of seeds of the 3-d reproduction (11.5%) and 5.1 th. htw of seeds of the mass reproduction (45.1%). It is necessary to increase the areas of varietal sowings of millet and to improve quality of sowing material for more efficient grain production.